Surface Properties Of Aluminium Oxide Support Layer Used For Vertically Aligned Single-Walled Carbon Nanotube Growth - Mohd Abid, Mohd Asyadi Azam; Abd Rashid , Mohd Warikh; Isomura , Kazuki; Fujiwara, Akihiko; Shimoda, Tatsuya (2012)
-